ANALISIS EKONOMI USAHA PEMBIBITAN MANGROVE DI KELOMPOK TANI DAN NELAYAN BERAS BASAH, KELURAHAN BEREBAS TENGAH KOTA BONTANG (Economic Analysis of Mangrove Nurseries in Farmers and Fishermen's Groups Beras Basah, Berebas Village, Central Bontang City) - DAU, ALVIYANI; SYAFRIL, MUHAMMAD; SUSILO, HERU (Universitas Mulawarman (University of Mulawarman), 2023)
The goal of the research is to measure the eligibility of mangrove cultivation carried out by Beras Basah farmers and fishermen group and to determine the supporting and inhibiting factors in mangrove cultivation business. The method that’s been used in this research is the method of economic eligibility analysis with R/C, BEP, PP, and ROI study approach method and descriptive analysis method. The results of the research show that the cultivation managed by the farmers and fishermen group in Beras Basah made a profit and are eligible, with an R/C value of 2.29, 6.570 of BEP productions, 876.04 of BEP pricing, 5,423,712 of BEP sales, 7.37 of PP and 40.72% ROI. The supporting factor in this cultivation are: 1). There’s assistance by the government officials, 2). Good cooperation among the group of farmers and fishermen, 3). The area of cultivation is free to use. The inhibiting factors to the cultivation are: 1). The public consumers’ demand are less, 2). There’s ocean tide that would affect the cultivation process.